Hypochlorous Acid as a Potential Postsurgical Antimicrobial Agent in Periodontitis: A Randomized, Controlled, Non-Inferiority Trial - Julio Cesar Plata; David Díaz-Báez; Nathaly Andrea Delgadillo; Diana Marcela Castillo; Yormaris Castillo; Claudia Patricia Hurtado; Yineth Neuta; Justo Leonardo Calderón; Gloria Inés Lafaurie (MDPI AG, 2023)
Background: Hypochlorous acid (HOCl) is an antimicrobial agent with high affinity to Gram-negative bacteria of the subgingival biofilm. It could have an equivalent or no inferiority effect to chlorhexidine (CHX) to avoid recolonization of these microorganisms after the post-surgical period. Objective: The objective is to compare the reduction of plaque index (PI), gingival index (GI), pocket depth (PD), gain of clinical attachment level (CAL), and bacterial recolonization of periodontopathic microorganisms in subgingival biofilm at 7, 21, and 90 days after Open Flap Debridement (OFD) under two antimicrobial protocols: (A) HOCl 0.05% followed by HOCl 0.025% and (B) CHX 0.2%/CHX 0.12% used per 21 days without regular oral hygiene during the post-surgical period. Material and methods: A no-inferiority randomized controlled trial was carried out. Thirty-two patients were randomly divided to receive each antiplaque protocol after OFD in patients with periodontitis. Clinical indexes and bacterial recolonization were assessed using qPCR for up to 90 days. Data were analyzed using repeated measures ANOVA, mixed effects models adjusted for treatment, time, and the Chi-squared/Fisher test. A no-inferiority analysis was also performed using the Hodges-Lehmann hypothesis test for non-inferiority. Results: HOCl was not inferior to CHX in reducing PI. Both groups showed a comparable reduction of recolonization for Porphyromonas gingivalis, Tannerella forsythia, and Eubacterium nodatum. However, the HOCl protocol was non-inferior to the CHX protocol for Treponema denticola and Aggregatibacter actinomicetemcomitans. Conclusions: HOCl improved periodontal healing. HOCl showed an impact in reducing the recolonization of periodontopathic bacteria in the postoperative period.